The impact of sleep, mental health, and gender on academic performance in Canadian university students - Kuhn, Tara; Heisz, Jennifer J.; Middleton, Laura E. (Frontiers in Education, 2025)
PurposeTo understand the independent and combined effects of sleep and mental health on academic performance, while also exploring gender differences.MethodsA cross-sectional survey was distributed to undergraduate students at two Canadian universities in March 2022. Sleep quality and quantity was assessed using the Pittsburgh Sleep Quality Index. Mental health variables included stress, depression, and anxiety. Academic performance was self-reported as students’ cumulative percent average. Multiple linear regressions were used to investigate how (1) sleep, (2) mental health, (3) sleep and mental health together related to academic performance. These analyses were then repeated, stratified by gender.ResultsA total of 1,258 undergraduate students participated. While mental health and sleep duration predicted academic performance among the whole sample, there were important gender differences. In gender-stratified data, sleep quality and quantity predicted academic performance in men but not mental health in the combined model. For women, stress, depression, and anxiety predicted academic performance but not sleep quality. Sleep duration squared, but not sleep duration simply, was associated with academic performance in women.ConclusionSleep and mental health are essential for academic performance in undergraduate students. Further, gender may play a critical role. Universities should consider gender-specific supports to improve the wellbeing of their students.